Adaptive Introgression as an Evolutionary Force: A Meta‐Analysis of Knowledge Trends - Pedro Horta; Helena Raposeira; Javier Juste; Orly Razgour; Hugo Rebelo (Evolutionary Applications)
ABSTRACT There is growing evidence for the role of introgressive hybridization in promoting species adaptation (i.e., adaptive introgression) owing to increasing genomic studies on a diversity of taxa over the past decades. However, introgressive hybridization was, and still is, regarded as a homogenizing process hindering the evolutionary process of adaptation to selection pressures. Despite methodological advances, key gaps remain in understanding how adaptive introgression due to hybridization functions across taxonomic groups and biological levels. This study has three objectives: (1) to explore historical trends in the understanding of adaptive introgression, particularly its genomic and functional dimensions; (2) to investigate structural organismal characteristics influencing patterns of adaptive introgression; and (3) to evaluate how adaptive introgression interacts with counteracting evolutionary mechanisms. We carried out a systematic review of the adaptive introgression literature and a multidimensional meta‐analysis. The current knowledge trends have been shaped by the genomic revolution. Since 2012, genomic studies have contributed to establishing a clearer understanding of adaptive introgression. The amount and variety of published studies increased from bacteria to mammals across a complexity gradient, focusing on the genomic level and progressively having consequences at a greater number of levels of biological organization (from physiological and demographic to behavioral/ecological). Testing for tendencies, our study also revealed evolutionary mechanisms linked to adaptive introgression co‐occurring with divergence forces, demonstrating that these processes are not mutually exclusive, even when they act in opposite directions, i.e., convergence and divergence, such as autosomal introgression (versus islands of differentiation in sex‐linked chromosomes), balancing selection (versus genetic drift), or sexual selection (versus assortative mating). This balance is mediated by environmental conditions as they are frequently reported in the studies, regardless of the organisms' structural complexity, shaping the path of the evolutionary process of introgressing species. Studying introgression patterns has important implications for understanding adaptation in rapidly changing environments.